From semicoordination to metal-involving halogen bonding in adducts of square planar dithiocarbamates with sym-triiodotrifluorobenzene; Химия и химическая технология в XXI веке; Т. 2 - Ivanov D. M. Daniil Mikhaylovich (Non-covalent interactions in crystalo-chemical design and supramolecular chemistry, 2021)
Заглавие с титульного экрана